Green synthesis of new chiral 1-(arylamino)imidazo[2,1-a]isoindole-2,5-diones from the corresponding α-amino acid arylhydrazides in aqueous medium - Bouzayani, Nadia; Kraїem, Jamil; Marque, Sylvain; Kacem, Yakdhane; Carlin-Sinclair, Abel; Marrot, Jérôme; Hassine, Béchir Ben (Beilstein Journal of Organic Chemistry, 2018)
New chiral 1-(arylamino)imidazo[2,1-a]isoindole-2,5-dione derivatives were obtained in good to excellent yields via the cyclocondensation of 2-formylbenzoic acid and various α-amino acid arylhydrazides using water as the solvent in the presence of sodium dodecyl sulfate as the surfactant and under simple and minimum manipulation, without purification. The reaction is totally diastereoselective and gives access to the nitrogenated tricyclic core with a relative trans stereochemistry.
Keywords: sodium dodecyl sulfate; totally diastereoselective; trans-stereochemistry